Monitoring and management of fibrosing interstitial lung diseases: a narrative review for practicing clinicians. (September 2021) - Nambiar, Anoop M.; Walker, Christopher M.; Sparks, Jeffrey A.
Close monitoring of patients with fibrosing interstitial lung diseases (ILDs) is important to enable prompt identification and management of progressive disease. Monitoring should involve regular assessment of physiology (including pulmonary function tests), symptoms, and, when appropriate, high-resolution computed tomography. The management of patients with fibrosing ILDs requires a multidisciplinary approach and should be individualized based on factors such as disease severity, evidence of progression, risk factors for progression, comorbidities, and the preferences of the patient. In this narrative review, we discuss how patients with fibrosing ILDs can be effectively monitored and managed in clinical practice.